Learning through Service and Volunteerism: The pedagogical Model in Higher Education in Finland in Degree Programme in Social Services - Eija Raatikainen (IJRDO- Journal of Educational Research, 2019)
This paper explores the voluntary work course (internship) in higher education, in Social Services Programme. It explores the learning outcomes of a course called “Internship in Voluntary Work” (five credits). The paper presents “The Pedagogical Model of Learning Volunteerism” that the course is based on. The paper also utilizes research of student learning outcomes of the course. Research questions are “What did you learn from volunteer work (internship)?” and “What do you think is the significance of volunteer work?” The data were collected during 2016-2017 and it included 134 participants (n=134). The data were analyzed with content analysis. The findings from the analysis of a digital self-evaluation form shows that students consider volunteer work (Internship) very significant not only for the society but also for their own learning and professional development. It seems to offer a possibility to learn wider skills and abilities than the curriculum shows. According to the results, the findings also shown, those students’ have learned many meta- and transversal skills (Heckman & Kautz 2012; Rodin & Levy 2015) during the internship.